2015
DOI: 10.1007/s00246-015-1133-5
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Family History and Phenotype–Genotype Correlation in Pediatric Brugada Syndrome: More Burden to Bear in Clinical and Genetic Diagnosis

Abstract: Brugada syndrome (BrS) is an autosomal-dominant genetic cardiac disorder caused in 18-30 % of the cases by SCN5A gene mutations and manifested by an atypical right bundle block pattern with ST segment elevation and T wave inversion in the right precordial leads. The syndrome is usually detected after puberty. The identification of BrS in pediatric patients is thus a rare occurrence, and most of the reported cases are unmasked after febrile episodes. Usually, having a family history of sudden death represents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
(14 reference statements)
0
7
0
1
Order By: Relevance
“…For untranslated variants located in the 3′UTR of SCN5A, recent studies reported that rs41310757, rs4073797, rs4073796, and rs41315485 affect gene expression by changing the binding site of miRNA (Zhao et al 2015;Daimi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For untranslated variants located in the 3′UTR of SCN5A, recent studies reported that rs41310757, rs4073797, rs4073796, and rs41315485 affect gene expression by changing the binding site of miRNA (Zhao et al 2015;Daimi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…SCN5A is located on chromosome 3p21 and encodes the type 5 α-subunit of the cardiac voltage-gated sodium channel (Na V 1.5) (Chen et al 1998). The Na V 1.5 protein, which is 80 kb in size and consists of 2016 amino acids, is expressed only in the heart (Daimi et al 2015). It is a pore-forming transmembrane protein consisting of four internal homologous domains (DI-DIV).…”
Section: Introductionmentioning
confidence: 99%
“…Algunas condiciones como los episodios febriles pueden desenmascarar formas silentes del SBr y/o conferir un riesgo incrementado (transitorio) de arritmias ventriculares (99), especialmente en la población pediátrica (100), donde la identificación del SBr es poco habitual y la mayoría de los casos reportados se desenmascaran después de episodios febriles (101).…”
Section: Manifestaciones Clínicas Y Diagnósticounclassified
“…Approximately 60% of patients with aborted sudden death with the typical BrS electrocardiogram have a family history of sudden death, or have family members with the same electrocardiographic abnormalities, supporting a familiar inheritance of the disease. However, sporadic cases of BrS have also been reported [3,4]. Genetic determinants of the BrS have emerged over the last decade [5].…”
Section: Introductionmentioning
confidence: 99%